Tele-health: bridging the gap between the need for rapid toxicology consultation and shortage in poison control centers - a unique experience in Dammam poison control center - K AlMazroua, Maha; Y Issa, Sahar; M Hafez, Essam (International Journal of Pharmacology and Toxicology, 2016)
The development of poisons control centers (PCCs) has in general complied with the actual needs and conditions in the society. A single MOH toll-free telephone number (937) for all health services enables rapid transfer of the caller to a specialist in poison information and toxicology anywhere in the Saudi Kingdom at any time, day or night. A board-certified, qualified toxicologist can be reached within a few moments. This remarkable system is maintained by the voluntary cooperation of the 45 technical members of the Regional Dammam Poison Control Center (DPCC) since nearly three years, being the only PCC in the Kingdom offering this service till date.Objectives: The objective of the current study is to empathize and promote services delivered by PCCs as poison control, chemical safety, prevention and treatment of toxicities within the Saudi Kingdom through the single MOH toll-free telephone number (937), being the only Saudi PCC responding to this service in toxicology. It promotes toxicovigilance in the hope of decreasing the overall morbidity and minimizing mortality from poisoning.Methods: The calls received on the hotline telephone number of the DPCC directly conveying the calls from the free MOH line (937), were retrospectively studied and evaluated. Themes that emerged from the data obtained from telephone communication were statistically assessed.Results: The study showed that the Unintentional exposures (N= 4353, 85%) greatly surpassed other types of exposure. Most of the callers were Saudi (N=4198, 82%) from Eastern region (N= 1654, 32.3%). The toxicological calls (N: 2389, 87.6%) were nearly 7 folds of the non-toxicological calls (N: 337, 12.4%) in the third year of the study. The number of calls were more during the summer season.